2021
DOI: 10.3389/fmicb.2021.682064
|View full text |Cite
|
Sign up to set email alerts
|

An Escherichia coli Effector Protein EspF May Induce Host DNA Damage via Interaction With SMC1

Abstract: Enterohemorrhagic Escherichia coli (EHEC) O157: H7 is an important foodborne pathogen that causes human diarrhea, hemorrhagic colitis, and hemolytic uremic syndrome. EspF is one of the most important effector proteins injected by the Type III Secretion System. It can target mitochondria and nucleoli, stimulate host cells to produce ROS, and promote host cell apoptosis. However, the mechanism of the host-pathogen interaction leading to host oxidative stress and cell cytotoxic effects such as DNA damage remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…From GO analysis, it indicated that EspF regulated the host metabolic and biological process for its colonization and infection. As for the cellular components part, it demonstrated EspF altered proteins were mostly located in the organelle and organelle part, which was consistent with our previous research that EspF targeted to the mitochondria and nucleus ( Zhao et al, 2013 ; Fu et al, 2021 ). The most predominant molecular function of EspF infection was binding.…”
Section: Discussionsupporting
confidence: 91%
“…From GO analysis, it indicated that EspF regulated the host metabolic and biological process for its colonization and infection. As for the cellular components part, it demonstrated EspF altered proteins were mostly located in the organelle and organelle part, which was consistent with our previous research that EspF targeted to the mitochondria and nucleus ( Zhao et al, 2013 ; Fu et al, 2021 ). The most predominant molecular function of EspF infection was binding.…”
Section: Discussionsupporting
confidence: 91%
“…Many cancer cells, such as ovarian cancer cells, are resistant to apoptosis and DNA damage, resulting in chemoresistance [ 54 ]. p-H2AX is a marker protein for DNA double-strand damage [ 55 ], and we evaluated the expression of p-H2AX to investigate whether DNA damage inhibition induced by HSP90AB1 overexpression is involved in cisplatin resistance. The DNA damage marker protein p-H2AX exhibited further elevated expression in HSP90AB1-inhibited cells in the presence of cisplatin and ME.…”
Section: Discussionmentioning
confidence: 99%
“…8-Oxoguanine (8-oxoG) and phosphorylated histone H2A variant H2AX are commonly used as biomarkers for oxidative DNA damage and double-strand breaks (DSBs) in colorectal cancer (CRC) ( 4 ). Although the tumorigenic potential of EHEC has been previously discussed ( 5 7 ), there is limited evidence of the mechanisms underlying the formation of oxidative DNA lesions.…”
Section: Introductionmentioning
confidence: 99%
“…We recently found that EHEC EspF led to multi-nucleation, hypertrophy, and phosphorylation of H2AX, core features of severe DNA damage. Moreover, the ATM downstream protein SMC1 was phosphorylated and shifted from the nucleus to the cytoplasm, inhibiting the activation of DDR ( 5 ). Interactions between EspF and mitotic arrest-deficient 2 like 2 (MAD2L2), the latter of which inhibits the Cdc20-related protein (Cdh1) and the anaphase-promoting complex, have been demonstrated, suggesting that EspF plays an essential role in cell cycle and mitotic control ( 7 , 42 45 ).…”
Section: Introductionmentioning
confidence: 99%